1997
DOI: 10.1071/bt96083
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Frequency Fire on Floristic Composition and Abundance in a Fire-prone Heathland near Sydney

Abstract: The effect of high frequency fire regimes on a coastal heathland north of Sydney was examined. Plant community composition and species frequency and density (of a subset of species) were compared among sites burnt by either one, two or three fires in the period 1988-1990 inclusive. Constrained ordination indicated that number of fires had a significant effect on floristic composition. Site variables also had a significant effect on floristics and frequency and accounted for a larger proportion of variation tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(104 citation statements)
references
References 18 publications
2
95
0
Order By: Relevance
“…The remaining variation (21%) represented confounding effects of the environmental predictors and fire treatments, which were largely due to burn coverage variation among treatments. Our findings support those from similar forests elsewhere, that both site factors, irrespective of fire history (Bradstock et al 1997;Henderson and Keith 2002;Lewis et al 2012) and fire frequency have an important influence on plant composition (Henderson and Keith 2002;Spencer and Baxter 2006;Watson et al 2009;Penman et al 2011b;Wittkuhn et al 2011). Our results suggest that species such as Alphitonia excelsa, Lantana camara, Cyclophyllum coprosmoides and Psydrax odorata are more likely to proliferate in long-unburnt areas than in frequently burnt forests.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The remaining variation (21%) represented confounding effects of the environmental predictors and fire treatments, which were largely due to burn coverage variation among treatments. Our findings support those from similar forests elsewhere, that both site factors, irrespective of fire history (Bradstock et al 1997;Henderson and Keith 2002;Lewis et al 2012) and fire frequency have an important influence on plant composition (Henderson and Keith 2002;Spencer and Baxter 2006;Watson et al 2009;Penman et al 2011b;Wittkuhn et al 2011). Our results suggest that species such as Alphitonia excelsa, Lantana camara, Cyclophyllum coprosmoides and Psydrax odorata are more likely to proliferate in long-unburnt areas than in frequently burnt forests.…”
Section: Discussionsupporting
confidence: 81%
“…The triennial burning treatment was more beneficial than the other two treatments for long-term persistence of acacias in this forest type. However, managers should consider less frequent fire regimes to encourage smaller obligate seed regenerators that may be completely scorched by fire and may require .3 years to germinate from seed and produce fruit before the next fire (Keith 1996;Bradstock et al 1997;Bradstock and Kenny 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some heaths on nutrient-poor shallow soils with high exposure to salt spray, such as those on the peak of Dover Island in Bass Strait, may need no fire to persist (Kirkpatrick 1995), while other heathlands clearly do. It is unwise to burn most Australian heaths at an interval of less than 8-10 years because of the potential loss of obligate seed regenerators (Bradstock and Myerscough 1981;Bradstock et al 1997;Gill and Stephens 2009), however, our results strongly suggest that too frequent fire is currently not a problem, and that more frequent planned burning should be undertaken in the coastal heathlands of south-eastern Tasmania. Furthermore, since different populations of the same species can vary in their capacity to resprout or regenerate from seed after fire, it may be more useful to consider the fire response at a population level, rather than considering species response traits individually (Vivian et al 2010).…”
Section: Discussionmentioning
confidence: 73%
“…Several authors (Bradstock et al, 1997;Pausas, 1999) showed that recurrent fires favoured seeders only if the fire interval enabled plant maturation and production of seeds. Some Pinus trees were present above the shrublands in one plot and in mixed stands.…”
Section: Resultsmentioning
confidence: 99%